Cost and implementation of mitigation in agriculture - Loboguerrero Rodriguez, Ana María (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Keynote presentation by Ana Maria Loboguerrero Rodriguez, CCAFS and the International Center for Tropical Agriculture (CIAT) International conference on agricultural emissions and food security: Connecting research to policy and practice 10-13 September 2018 Berlin, Germany